THE INFLUENCE OF EMPLOYEE ENGAGEMENT MEDIATION ON THE PERFORMANCE OF HEALTH WORKERS AT THE SABANG CITY REGIONAL GENERAL HOSPITAL - Husnaina Mailisa Safitri; Agus Ariyanto; Yukrian (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to elaborate on the mediating effect of employee engagement on the performance of healthcare workers at the General Hospital of Sabang City. The research sample was taken from the employees of the General Hospital of Sabang City using the Slovin formula for sample calculation and a simple random sampling technique, resulting in 181 employees as the observed sample. The data analysis techniques used include path analysis, outer model analysis, inner model analysis, and hypothesis testing with the help of SmartPLS 4.1.0.5 software. Employee engagement has a significant positive relationship with employee performance. Happiness at work significantly influences employee engagement. Happiness at work does not have a significant impact on employee performance. Incentives have a significant positive relationship with employee engagement. Incentives do not have a significant impact on employee performance. Transformational leadership has a very strong and significant positive relationship with employee engagement. Transformational leadership has a significant positive relationship with employee performance. Happiness at work has a significant positive impact on employee performance through employee engagement. Incentives have a significant positive impact on employee performance through employee engagement. Transformational leadership has a significant positive impact on employee performance through employee engagement at the General Hospital of Sabang City.